THE ROLE OF CONSUMER EDUCATION AND AWARENESS IN SHAPING MARKETING EFFECTIVENESS - Bharathi K V; Amruthamma R (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study aims to establish the impact of consumer education and awareness in marketing communication. This research employs a systematic secondary qualitative research approach and thematic analysis of the existing literature, industry reports, and case studies to assess the relationship between educational initiatives and consumer behavior as well as the resultant brand effects. Consequently, research findings depict educational forms of marketing as pivotal in increasing consumers’ awareness and understanding of the targeted brands and products. Honest and open communication becomes essential to the development of confidence and consumer engagement. Further, it points out issues including but not limited to information overload and opportunities for the creation of innovative learning models. In general, the study highlights the implications of consumer knowledge in molding the marketing effectiveness and indicates the further research directions to investigate the impact of the educational marketing in the long run and the role of cultural factors in the perception of the target audience.